Nudging als politisches Instrument: Gute Absicht oder staatlicher Übergriff? - Lisa V. Bruttel; Florian Stolley; Werner Güth; Hartmut Kliemt; Steven Bosworth; Simon Bartke; Jan Schnellenbach; Joachim Weimann; Marlene Haupt; Lothar Funk (Wirtschaftsdienst, 2014)
Die Verhaltensökonomie und ihre praktischen Implikationen geraten immer stärker in den Fokus auch der deutschen Politik. Individuelle Entscheidungen sollen im Sinne eines "libertären Paternalismus" sanft beeinflusst werden. Die 'Nudges' bestehen in Standardvorgaben, Selbstbindungen und der Informationsbereitstellung. Deren Anwendung setzt allerdings die Klärung einiger Fragen voraus: Wer darf sich anmaßen, für die Wirtschaftssubjekte 'kluge' Entscheidungen zu treffen? Bei welchen Entscheidungen sind Eingriffe einer anderen Instanz begründbar? Mit welchem Zeithorizont und aufgrund welcher Wohlfahrtsüberlegungen wird eine Entscheidung als 'richtig' defi niert? Welcher Rationalitätsbegriff steht hinter dem Konzept? – – Behavioural economics and economic experiments can offer valuable insights to policymakers. Liberal or soft paternalism assumes that governmental nudging through the conscious setting of defaults in order to overcome potential behavioural anomalies can lead to better outcomes without giving up basic freedom of choice. Some authors recommend state interventions to prevent commercial firms from exploiting the effects of nudges, in particular through the use of defaults. They consider it necessary to create mandatory rules for how the nudging is permitted to be done. The state must decide on the scope and limits of the commitment power it grants to individuals. The danger of nudging is that information asymmetries can be used in order to manipulate people. The authors see nudges in the form of information provision and those for voluntarily improving self-control as useful. Educating individuals about the pitfalls of rational decision-making and using individual-level private mechanisms to avoid such pitfalls is put forward as a promising approach. Regarding paternalism as well as soft paternalism as enemies to freedom, liberal economists reject such state interference.
Keywords: D03; D18; D60; D80; 330; Politische Entscheidung; Soziales Verhalten; Verhaltensökonomik; Deutschland